Effects of Child Marriage on Education and Health of Women in Rural Naogaon District of Bangladesh: A Conceptual Analysis (American Journal of Interdisciplinary Research and Innovation, 2024)
Child marriage is a pressing global concern, and Bangladesh is no exception to this social reality. Undoubtedly, child marriage significantly hinders worldwide women’s empowerment, constituting a severe violation of human rights. In developing countries, including Bangladesh, as a result of child marriage on education and health, social indicators of women’s empowerment are affected, which creates obstacles to reaching sustainable development goals. The main purpose of this study is to identify the effects of child marriage on education and health of women and explore the relationships among child marriage, women empowerment and sustainable development goals. A mixed methodology was applied to this study. By using Snowball sampling techniques, data was collected from 35 respondents 4 male and 31 female, who were read in primary (27) and secondary (8) school.The findings of the study identified that the education and health of women in Naogaon at Sapahar are seriously affected due to child marriage. As a result of child marriage, girls are dropping out of school, deprived of education, creating gender inequality, and hampering women’s empowerment; on the other hand, girls are losing physical and mental health, suffering malnutrition and long-term health diseases, increasing their risk of maternal and child mortality. We was found child marriage as the main and only reason for female students dropping out of school both Primary and secondary school Here, 100 percent of the total female respondents dropped out of child marriage. The health condition of the girl’s respondents of this study is more vulnerable because the girl’s age of marriage is very low. In the study area, the average age of marriage of total respondent was 13, (the age of male respondentis 15 and female student was 11). Lowest age of female was 9 (eleven case) and lowest age of male was 14 (two case). These findings can serve as valuable insights for academics and policymakers, guiding the development of effective plans and programs to address child marriage. Ultimately, the goal is to contribute to achieving sustainable development goals (SDGs) and creating a better future for women in Bangladesh.